Ciptaningrasa Bojongan Sebagai Bentuk Prototype Edukasi Visual - Lalan Ramlan; Jaja Jaja (JPKS (Jurnal Pendidikan dan Kajian Seni), 2023)
Jaipongan by Gugum Gumbira has become a separate dance genre, has four types of movements as dance constructions, among others; bukaan, pencugan, nibakeun, and mincid used in each dance repertoire. The dance construction has high elasticity or flexibility, because there is no set stiffness. However, in the dynamics of its development outside of Jugala production, it is increasingly losing its entity, because background dances with Jaipongan nuances are often called Jaipongan dances. In connection with this, the problems raised in the research of works of art with the title "Ciptaningrasa Bojongan" are formulated as follows: How to create a dance model as a prototype form with visual education and how to implement it to the public. In connection with the research question, a theory with the instrumental aesthetic paradigm was used which explains that all art objects or events contain three main aesthetic elements, namely; appearance, content, and presentation. In line with this paradigm, in its operation it uses qualitative methods with descriptive analysis techniques, namely "the data collected is in the form of words, pictures, and not numbers, then analyzed theoretically and presented in a narrative to convey the results of new studies". The results achieved are a model of artwork with a renewal of as a form of visual education prototype in the value transformation process; revive, activate, and / or re- function impressively new forms, positions and contexts to society